An overview of the history of wind turbine development: Part II–The 1970s onward. Issue 1 (February 2023) - Gipe, Paul; Möllerström, Erik
We review the development of wind turbines for generating electricity from the late 19th century to the present, summarizing some key characteristics. We trace the move from two and four blade wind turbines to the three blades common today. We establish that it was not the governmental-funded wind programs with its large-scale prototypes of the 1970–80s that developed into the commercial turbines of today. Instead, it was the small-scale Danish wind turbines, developed for an agricultural market, that developed into the commercial turbines of today. And we show that much of what we know today about wind turbine design was known by the 1930s and certainly well known by the late 1950s. This work is divided into two parts: the first part takes up the development from the first electricity producing wind turbines through to the 1960s and a second part on development from the 1970s onward.